Analysis of the Impact of Fiscal Decentralization on Income Inequality in Indonesia - Dardiri, Gio Vannie Innocentie; Fazaalloh, Al Muizzuddin (Journal of Development Economic and Social Studies, 2026)
Fiscal decentralization in Indonesia leaves a reasearch gap regarding its effectiveness in addressing regional income disparity. This study aims to analyse the impact of fiscal decentralization on income inequality by examining non-linier relationships and spatial dynamics between Java and Non-Java regions. Using Fixed Effects panel data analysis across 34 provinces from 2015-2024, a significant U-Shaped relationship was identified. Initially, decentralization reduces inequality, but beyond a threshold, increased fiscal autonomy widens the gap due to differing regional capacities. This pattern is spatially consistent, with Java showing higher vulnerability. In conclusion, the effectiveness of decentralization depends on balancing authority with institutional capacity building. This research contributes to the reformulation of fiscal transfer policies to mitigate economic divergence.